Resounding: Feeling, Mytho-ecological Framing, and the Sámi Conception of Nature in Outi Tarkiainen’s The Earth, Spring’s Daughter - Torvinen, Juha (MUSICultures, 2019)
The song-cycle The Earth, Spring’s Daughter by the Finnish composer Outi Tarkiainen (born in 1985) is based on poems in the Northern Sámi language by Nils-Aslak Valkeapää and Rauni Magga Lukkari, among others. This ecomusicological and cultural musicological article analyzes the musical-textual ways the work portrays Sámi culture’s changing relationship to nature and addresses today’s environmental concerns. Typical for the work are musical motifs with nature-related meaning, representations of the cyclical conception of time, and adaptations of Sámi mythology for communicating environmental(ist) messages. The distinctive way the work grounds the sense of nature in feelings is called “mytho-ecological framing.”